# Yahoo Web Search

1. Sort by

1. ### need help r-2x = 14 for s?

r - 2s = 14 Solve for s: Subtract r off both sides: -2s = 14 - r Multiply both sides by -1 to avoid trouble later: 2s = r - 14 Divide by 2: s = (r - 14)/2

5 Answers · Science & Mathematics · 21/09/2012

2. ### Determine the r-values?

r^2h)/(2πrh+2πr^2)<1/3 (πr^2)/(2πr+2πr^2)<1/3 (πr^2)/2πr(1+r)<1/3 r/2(1+r)<1/3 r<...

2 Answers · Science & Mathematics · 24/08/2012

3. ### Express (7r+10)/r(r+1)(r+2) in partial fractions?

(7r + 10)/r(r + 1)(r + 2) = A/r + B/(r + 1) + C/(r + 2) A(r + 1...(r + 1) = 7r + 10 r = 0 --> 2A = 10 --> A = 5 r = -1 --> -B = 3 --> B = -3 r = -2 --> 2C = -4...

1 Answers · Science & Mathematics · 03/01/2013

4. ### math equation ( what does r=?)?

The answer is r= -.5 I didn't know if you wanted the explanation or not but I...: 2r=-1 Divide 2r by both sides and the answer is r=-1/2 or -.5

2 Answers · Science & Mathematics · 14/10/2010

5. ### Quadratic, how to solve for R?

Simplify: (square the top and bottom of the fraction, then multiply top by R: 22.4 = 14400R/(R+139)^2 Clear fraction: (multiply both ...

2 Answers · Science & Mathematics · 21/10/2009

6. ### what does (1+r/m)^m tend to as m tends to infinity? Thanks!?

(1+r/m)^m (1+1/(m/r))^m (1+1/(m/r))^mr/r (1+1/(m/r))^r(m/r) as m -> infin, so does m/r (1+1/(m/r))^r(m/r) This is e^r Lets evaluate the limit mathematically...

3 Answers · Science & Mathematics · 03/12/2008

7. ### VB : R = A + Csquared?

R=A + C^2 R-A= C^2 + or - sqrt(R-A) =C C=sqrt(R-A) or C=-sqrt(R-A)

2 Answers · Science & Mathematics · 30/08/2007

8. ### how to solve r^2+3r=5?

R= 1.1926, -4.1926 Try using MathWay.com Hope this helps!

4 Answers · Science & Mathematics · 07/04/2013

9. ### Show that ∑(n+ r-1)(n+r) = (1/3n)(7n^2 – 1)?

∑ _{r=1, n} 1= n ∑ _{r=1, n} r= (n+1)·n/2 ∑ _{r=1, n} r²= n·(n+1)·(2n+1)/6 ==>...2nr +r² -n -r) = (n²-n)·∑ _{r=1, n} 1 + (2n-1)· ∑ _{r=1, n} r + ∑ _{r=1, n} r² = (n²-n)·n + (2n-1)·(n...

1 Answers · Science & Mathematics · 26/07/2009

10. ### Find x Value for R-C?

R=4x^2+8x C=x^2+2x R-C= 3x^2+6x (R-C)'= 6x+6 (R-C)"= 6 Now (R-C...

2 Answers · Science & Mathematics · 13/09/2013

1. Try asking your question on Yahoo Answers